HUBUNGAN BODY IMAGE DENGAN SELF-ACCEPTANCE SISWA SERTA IMPLIKASINYA DALAM LAYANA BIMBINGAN DAN KONSELING: Body Image, Self-Acceptance - Riska Andriani; Oktafiana Kiranida; Ainul Husna; Reggiana Brescia; Putri Waliyyan (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This study aims to describe the picture of Body Image and self-acceptance and describe the picture of the relationship between body image and self-acceptance. The research method used is quantitative descriptive correlation. The number of samples in this study was 107 respondents. The instruments used in the study were the body image scale (X) and the self-acceptance scale (Y). The results showed that body image had a percentage of 67% of students having a moderate body image and self-acceptance of 59% of students having moderate self-acceptance. Body image and self-acceptance showed a significance value of 0.000 <0.05 with a value of r = 0.626, meaning that this value indicates a positive relationship, which means that the higher the body image a student has, the higher the level of self-acceptance in students, H₀ is rejected and H₁ is accepted. Thus, it can be concluded that there is a significant relationship between body image and self-acceptance. The implications of guidance and counseling services in this study are that BK teachers can provide information services in a classical format, content mastery services, role-playing, group guidance services and individual counseling for a more personal approach in helping students recognize negative thoughts to improve students' body image and self-acceptance.